Aspectos psicossociais da condição de torcedor de futebol - Sousa, Daniel Vitor Gomes de (2014)
Cheering for a football team is well known practice in many countries. In Brazil is an important phenomenon for their cultural impact, commercial, and for being part of a frequent presence on interpersonal relations in various contexts. Also, football, in various aspects, is privileged subject in media. Curiously, very few studies are available about the fans and for the most part, refer to the phenomenon of violence during the games, which is associated with specific groups of fans. The study sought to identify aspects that are recognized by fans as influences that have become fans and to continue to act as such. 395 patients, 266 men (67.3%) and 129 women (32.7%) with mean age of 28.4 years (SD = 7.81), all over 18 years old. Predominated participants living in the southeast region of the country (from 368 to 93.2%), mostly supporters of teams of Minas Gerais (Cruzeiro - Atlético and 29.4% - 26.6%). Demographic data were collected, information on the preferred team were collected, and an instrument was developed to measure aspects recognized by participants as relevant to their practice football fan. Original instrument consisted of 72 items to be answered on the standard 5-point Likert (1 - Does not characterize me; 5 - I fully characterized) which looked at three broad thematic categories: family, media, and other social contexts. The instrument and the sociodemographic questionnaire were made available on Internet sites related to the universe of football fans. Data were organized and analyzed it using SPSS - version 18.0. Factorial analysis of principal components was performed to verify the adequacy of the data and survey indicators of factorial validity of the measure. The accuracy rate of the four factors was 0.72, confirming the statistical reliability of Condition Fan Football and the internal consistency of the measure in the version with 33 items. The Dimension of Indirect Interaction (DII), Dimension Direct Interaction (DID), Dimension Media Pro Time (DMPro) and Dimension Media Counter-Time (DMCon) factors, with values of Cronbach's Alpha, respectively, 0.79, 0.89, 0.71 and 0.85, all considered satisfactory. The composition of each factor and the differences between them are the subject of discussion, as well as differences in the responses of men and women. The results show the validity and sensitivity of the measured composition of the condition of football fan developed.